Denaturation of whey proteins of milk during ohmic heating - Pereira, Ricardo Nuno Correia (2009)
Ohmic heating is receiving increasing attention from the dairy industry, once it is considered to be an alternative for the indirect heating methods of milk pasteurization. Milk proteins are probably the most affected constituents by heating and some of the changes may involve interaction with sugars, aggregation of casein micelles or association of whey protein aggregates with casein micelle surface through formation of the beta-lactoglobulin - k-casein complex. However, very limited information is available on the effects that the presence of moderate electric fields during heating may have on denaturation processes of milk proteins. The aim of this work is to evaluate the denaturation of the main whey proteins of bovine milk during ohmic heating. Raw bovine milk samples were heated at different temperatures (75, 80 and 85 ºC) using different heating rates and holding times (up to 30 minutes). Ohmic heating experiments were also adapted to simulate the sample temperature changes during conventional (indirect heating) experiments. Micro-differential scanning calorimetry (micro-DSC) was used to determine denaturation level and denaturing temperatures of the main whey proteins of bovine milk, such as beta-lactoglobulin and alfa-lactalbumin, by means of thermal analysis. Non-denaturating gel electrophoresis was also applied in order to detect any changes on the charge and hydrodynamic size of proteins. Our results show that the presence of moderate electric fields during heating, when compared with conventional heating experiments, did not enhance protein denaturation. Two endothermic peaks were found in micro-DSC heating curves of samples subjected to the ohmic heating treatment at 85 ºC during 30 s; thermal transitions were observed at 41 ºC and 71ºC eventually corresponding to the denaturation of alfa-lactalbumin and beta-lactoglobulin, respectively. Native electrophoretic bands also revealed that most of alfa-lactalbumin and beta-lactoglobulin changed to a denatured state after heating treatments of up to 15 minutes at 85 ºC.